Спільнота "мешканців" секвестрів Гетьманщини у світлі історико-демографічних характеристик - Сапронов, А. (Краєзнавство, 2017)
У статті на основі історико-демографічних характеристик аналізується спільнота в'язнів секвестрів Гетьманщини середини ХVІІІ ст. Підраховано кількість ув'язнених, досліджено статеву та
соціальну структури арештантів. Окрему увагу було приділено злочинам, скоєними жінками. Також
охарактеризовано вікову структуру і стан здоров'я ув'язнених. In the article analyzes the community of prisoners in the middle of the 18th century in Hetmanschyna based
on historical demographic characteristics. The number of prisoners has been calculated, the sexual and social
structures of the prisoners have been investigated. Particular attention was paid to crimes committed by women.
In this article also describes the age structure and state of health of prisoners.
Analysis of the structure of the prisoners provides interesting material for further generalizations and
formulating common trends of Hetmanschyna’s society in the middle of the 18th century. В статье на основе историко-демографических характеристик анализируется сообщество заключенных секвестров Гетманщины середины XVIII века. Подсчитано количество заключенных, исследованы половая и социальная структуры арестантов. Отдельное внимание было уделено преступлениям, совершенными женщинами. Также охарактеризованы возрастная структура и состояние здоровья заключенных.